DAMPAK PERDAGANGAN SISTEM ELEKTRONIK DALAM PERSPEKTIF SIYASAH SYAR’IYYAH - Wahyuni, Wilda Sri; Tenripadang, Andi; Mustarin, Basyirah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
The research discusses the impact of trade through electronic systems on business actors and consumers in the view of siyasah syar’iyyah, especially in Makassar City. The research method used is field research with juridical, theological syar’i, and sociological approaches. The results obtained: 1) The positive impact of trade through electronic systems on business actors and consumers is that it is easier to promote goods, easier to obtain consumers, wider market reach, easier shopping, energy and time saving. While the negative impacts can be unilateral cancellations, fictitious orders, defective products, and goods not in accordance with the image; 2) Trade through electronic systems is allowed in Islam, as long as it does not contain elements of usury, gharar, fraud, coercion, maisir and is not a forbidden item.